PENGARUH LINGKUNGAN, MOTIVASI DAN DISIPILIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN ABDI NUSA PALEMBANG - Husin, Husin (Jurnal Manajemen, 2019)
This study aims to determine the influence of the environment, motivation and discipline of employee productivity Abdi Nusa Palembang. In this study the number of population is 33 people all of the research sample. The samples in this study using techniques saturated samples. The results of this study are significant environmental influence, motivation and discipline on employee productivity Abdi Nusa Palembang regression model Ῡ X1 = 1.460 + 0.255 + 0.386 + 0.167 X2 X3 + e. Those variables go hand in hand with the dependent variable means that the higher the environment, motivation and discipline the higher the productivity of employees Abdi Nusa Palembang. There is a significant impact on employee productivity environment Abdi Nusa Palembang with sig 0.044 <α 0.05. There is a significant influence motivation to work productivity klaryawan Abdi Nusa Palembang with sig 0.001 <α 0.05. There was no significant effect on the productivity of employees disciplined Abdi Nusa Palembang Sig value 0.192> α 0.05